Stability of Islamic versus conventional banks: a Malaysian case - Muhamad Azhari Wahid,; Humayon Dar, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The purpose of this paper is to raise certain questions within the Malaysian banking sector and find the appropriate answers. The research questions of this paper are: a) whether Islamic banks are more stable relative to conventional banks; and b) what are the determinants of stability for both types of banks? In measuring and comparing the stability of Islamic and conventional banks, this study employs the financial soundness indicators (FSI) of the International Monetary Funds (IMF) and the z-score index. These are then followed by a series of parametric and non-parametric tests. Thereafter, a pooled ordinary least squares (OLS) robust regression is applied to examine the determinants of stability for Islamic and conventional banks. The results reveal that Islamic banks are significantly less stable than conventional banks. However, when the analysis is conducted based on a sample of small and large banks, the results suggest that only large Islamic banks are less stable than large conventional banks. In contrast, small Islamic banks are found to be more stable than small conventional banks. Furthermore, the results reveal that bank size, the level of capitalisation and income diversification are important determinants for the stability of Malaysian Islamic and conventional banks.